Precocious puberty under stressful conditions: new understanding and insights from the lessons learnt from international adoptions and the COVID-19 pandemic - Street, Maria Elisabeth; Ponzi, Davide; Renati, Roberta; Petraroli, Maddalena; D’Alvano, Tiziana; Lattanzi, Claudia; Ferrari, Vittorio; Rollo, Dolores; Stagi, Stefano (Frontiers in Endocrinology, 2023)
Neuro-biological variations in the timing of sexual maturation within a species are part of an evolved strategy that depend on internal and external environmental conditions. An increased incidence of central precocious puberty (CPP) has been described in both adopted and “covid-19 pandemic” children. Until recently, it was hypothesised that the triggers for CPP in internationally adopted children were likely to be better nutrition, greater environmental stability, and improved psychological wellbeing. However, following data collected during and after the coronavirus (COVID-19) global pandemic, other possibilities must be considered. In a society with high levels of child wellbeing, the threat to life presented by an unknown and potentially serious disease and the stressful environment created by lockdowns and other public health measures could trigger earlier pubertal maturation as an evolutionary response to favour early reproduction. The main driver for increased rates of precocious and rapidly progressive puberty during the pandemic could have been the environment of “fear and stress” in schools and households. In many children, CPP may have been triggered by the psychological effects of living without normal social contact, using PPE, being near adults concerned about financial and other issues and the fear of getting ill. The features and time of progression of CPP in children during the pandemic are similar to those observed in adopted children. This review considers the mechanisms regulating puberty with a focus on neurobiological and evolutionary mechanisms, and analyses precocious puberty both during the pandemic and in internationally adopted children searching for common yet unconsidered factors in an attempt to identify the factors which may have acted as triggers. In particular, we focus on stress as a potential factor in the early activation of the hypothalamic-pituitary-gonadal axis and its correlation with rapid sexual maturation.